Chow-Chow (Sechium edule): Best Alternative to Shifting Cultivation in Mizoram - Singh, B. K.; Ramakrishna, Y; Verma, V. K. (Indian Journal of Hill Farming, 2016)
Chow-chow (Sechium edule, iskut in Mizo dialect) is a boon crop of Mizoram and has potential for improving the socio-economic status of the tribal community. It is one of the most popular vegetables grown for its fruits, tender shoots, young leaves and the tuberized roots. Low calorific value of fruits makes it suitable for hospital diets/ baby foods and could also supplement to potatoes for diabetic patients. The vines climbs by clinging with tenacious tendrils, flowers are monoecious, fruits are mostly solitary, pear shaped, single seeded, viviparous with fairly bland taste of potato and cucumber. Mostly it is being cultivated on hilly terrain and the vines are trained over bower system, and even the hills having >100 % slope, where no cultivation is possible, is also under chow-chow cultivation. A flagship programme on commercialization of chow-chow cultivation in Mizoram will not only be an alternative to shifting cultivation; but also help in sustaining the farmers’ livelihood, reducing the runoff and soil erosion, and conserving the natural resources.